The Role of Glycosylation in Breast Cancer Metastasis and Cancer Control - Kölbl, Alexandra C.; Andergassen, Ulrich; Jeschke, Udo (Frontiers in Oncology, 2015)
Abstract Glycosylation and its correlation to the formation of remote metastasis in breast cancer had been an important scientific topic in the last 25 years. With the development of new analytical techniques new insights were gained on the mechanisms underlying metastasis formation and the role of aberrant glycosylation within. Mucin-1 and Galectin were recognized as key players in glycosylation. Interestingly, aberrant carbohydrate structures seem to support the development of brain metastasis in breast cancer patients, as changes in glycosylation structures facilitate an overcoming of blood-brain barrier. Changes in the gene expression of glycosyltransferases are the leading cause for a modification of carbohydrate chains, so that also altered gene expression plays a role for glycosylation. In consequence, glycosylation and changes within can be useful for cancer diagnosis, determination of tumour stage and prognosis, but can as well be targets for therapeutic strategies. Thus, further research on this topic would worth wile for cancer combating.